Heat transfer and pressure drop in a smooth and ribbed turn region of a two-pass channel. (25th June 2015) - Wang, Chenglong; Wang, Lei; Sundén, Bengt
Abstract: In the present study, the heat transfer and pressure drop in the turn region of a two-pass channel have been investigated experimentally. The liquid crystal thermography method is utilized to measure local heat transfer rates. Eight cases were tested, including one smooth, and seven different rib-roughened turn surfaces. The tested Reynolds numbers are 20, 000 and 26, 000, respectively. Results indicate that the heat transfer on the smooth outer wall is dominated by the flow impingement. When ribs are fitted onto the outer wall, the heat transfer patterns are significantly altered. However, the presence of ribs augments the heat transfer at the penalty of increased heat transfer non-uniformity and pressure loss. In order to provide optimized rib configurations, the thermal performance is evaluated, which balances the enhanced heat transfer and increased pressure loss. The results can be used for the development of cooling techniques in gas turbines and validation of numerical simulations. Highlights: Heat transfer in the smooth turn region is dominated by flow impingement. Ribs augment the heat transfer with increased thermal gradient and pressure loss. Comparisons between the present study and published data are presented. Thermal performances are evaluated and compared. Local measurements by liquid crystal thermography.